2015
DOI: 10.21836/pem20150302
|View full text |Cite
|
Sign up to set email alerts
|

Lying behaviour of group-housed horses in different designed areas with rubber mats, shavings and sand bedding

Abstract: Summary: One of the biggest concerns about group housing of horses is insufficient or interrupted lying behaviour, which might lead to sleep deprivation, and as a consequence thereof reduced performance and health. To address this concern the lying behaviour of 56 horses in a modern group housing system over four seasons was studied. This paper focuses on the lying behaviour of horses on different bedding materials. The reason behind is that rubber mats instead of natural bedding material have recently found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 6 publications
2
31
0
1
Order By: Relevance
“…Lying times were not quantified while these horses were within the paddock, which may explain the differences observed in lying time between that study 34 and the present study. In a study 33 examining the effect of housing type on lying bouts and lying time, maximum lying time was approximately 90 min/d for group-housed horses, which is similar to the posttreatment lying times in the present study. We believe that these results collectively indicate that the lying behaviors of the control and treated horses did not reflect diminished welfare.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Lying times were not quantified while these horses were within the paddock, which may explain the differences observed in lying time between that study 34 and the present study. In a study 33 examining the effect of housing type on lying bouts and lying time, maximum lying time was approximately 90 min/d for group-housed horses, which is similar to the posttreatment lying times in the present study. We believe that these results collectively indicate that the lying behaviors of the control and treated horses did not reflect diminished welfare.…”
Section: Discussionsupporting
confidence: 80%
“…32 The lying behavior of horses has been used to establish the welfare implications of housing horses in groups on wood shavings or rubber mats with shavings, in a shelter with sand, or in a sand paddock. 33 Lying time has been used to assess stress induced by housing horses in tie stalls, box stalls, or groups. 34 Results of these studies 33,34 indicate that behavioral changes can be used to assess the stress or pain induced in horses by various managerial strategies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This was also mentioned in a study of Zeitler-Feicht and Muggenthaler (2013) with horses in a group housing system, who preferred significantly an area with shavings for lying down and as place of residence than rubber bedding mats. This was confirmed by Baumgartner et al (2015), who found out that the daily total lying time per horse was significantly longer on shavings than on rubber mats with shavings covered. Factors such as depth, softness, texture, smell and insulating properties of the bedding material also influence the lying behaviour of horses (Rieman Pedersen et al 2004).…”
Section: Introductionmentioning
confidence: 60%
“…In the wild, horses move about in herds grazing for 20 or more hours a day and sleep for very short amounts of time, usually standing up. Equine ethologists say that domesticated horses only sleep for 3 hours a day, and usually only for very short periods of time, but that stable conditions affect the details of horses' sleep patterns (see, for example, Baumgartner et al 2015). I have often (quietly) witnessed horses lying down to sleep for more than 30 minutes especially in the afternoon or evening.…”
Section: Work-lives Are Also Social Livesmentioning
confidence: 99%